A macroeconomia do Social Desenvolvimentismo: um estudo da Rede Desenvolvimentista - Moraes, Isaías Albertin De [UNESP] (Instituto de Economia da Universidade Estadual de Campinas; Publicações, 2023)
This article has social developmentalism as its unit of analysis. The category of analysis is its macroeconomics. The study adopted as a methodological procedure the systematic approach by the selection, classification, and critical evaluation of bibliographic that form the theoretical framework of Social Developmentalism, especially the studies of Rede Desenvolvimentista (Rede D). The article was divided into two sections: the first presents a brief history of the building of the school and the conceptual operationalization of Social Developmentalism; the second focuses on elucidating the Social Development macroeconomics. The results of the research show that Social Developmentalism rescues the political character in macroeconomics by defending a model of macroeconomic policy and regime that is more adaptable and less fixed, but without embarking on “adventures” or “populisms.” The model, thus, contributes to the maturation of the developmentalism studies in Brazil nowadays.

O presente artigo tem como unidade de análise o Social Desenvolvimentismo. A categoria de análise é sua macroeconomia. O estudo adotou como procedimento metodológico a abordagem sistemática por meio da seleção, do fichamento e da avaliação crítica de dados bibliográficos que formam o arcabouço teórico do Social Desenvolvimentismo, sobretudo os estudos da Rede Desenvolvimentista (Rede D). O artigo foi dividido em duas seções: a primeira apresenta uma breve história da edificação da escola e da operacionalização conceitual do Social Desenvolvimentismo; a segunda seção concentra-se em elucidar a macroeconomia do Social Desenvolvimento. Os resultados da pesquisa demonstram que o Social Desenvolvimentismo resgata o caráter político na macroeconomia ao defender um modelo de política e de regime macroeconômico mais adaptável e menos engessado, no entanto sem enveredar para “aventuras” ou “populismos”. O modelo, assim, contribui para o amadurecimento do debate desenvolvimentista no Brasil atualmente.
The macroeconomics of Social Developmentalism: a study of Rede Desenvolvimentista
Keywords: Economic development; Social developmentalism; Economic development strategies; Macroeconomics; Brazilian economy; Economic development; Social Desenvolvimentismo; Estratégias de desenvolvimento econômico; Macroeconomia; Economia brasileira